New mitogenome and nuclear evidence on the phylogeny and taxonomy of the highly zoonotic tapeworm Echinococcus granulosus sensu stricto - Kinkar, Liina; Laurimae, Teivi; Sharbatkhori, Mitra; Mirhendi, Hossein; Kia, Eshrat Beigom; Ponce-Gordo, Francisco; Saarma, Urmas (Elsevier Science Bv, 2017)
Cystic echinococcosis, a zoonotic disease caused by Echinococcus granulosus sensu lato (s.l.), is a significant global public health concern. Echinococcus granulosus s. l. is currently divided into numerous genotypes (G1-G8 and G10) of which G1-G3 are the most frequently implicated genotypes in human infections. Although it has been suggested that G1-G3 could be regarded as a distinct species E. granulosus sensu stricto (s. s.), the evidence to support this is inconclusive. Most importantly, data from nuclear DNA that provide means to investigate the exchange of genetic material between G1-G3 is lacking as none of the published nuclear DNA studies have explicitly included G2 or G3. Moreover, the commonly used relatively short mtDNA sequences, including the complete coxl gene, have not allowed unequivocal differentiation of genotypes G1-G3. Therefore, significantly longer mtDNA sequences are required to distinguish these genotypes with confidence. The main aim of this study was to evaluate the phylogenetic relations and taxonomy of genotypes G1-G3 using sequences of nearly complete mitogenomes (11,443 bp) and three nuclear loci (2984 bp). A total of 23 G1-G3 samples were analysed, originating from 5 intermediate host species in 10 countries. The mtDNA data demonstrate that genotypes G1 and G3 are distinct mitochondrial genotypes (separated by 37 mutations), whereas G2 is not a separate genotype or even a monophyletic cluster, but belongs to G3. Nuclear data revealed no genetic separation of G1 and G3, suggesting that these genotypes form a single species due to ongoing gene flow. We conclude that: (a) in the taxonomic sense, genotypes G1 and G3 can be treated as a single species E. granulosus s. s.; (b) genotypes G1 and G3 should be regarded as distinct genotypes only in the context of mitochondrial data; (c) we recommend excluding G2 from the genotype list. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Cystic echinococcosis; Echinococcus granulosus sensu stricto; Echinococcus taxonomy; Hydatidosis; Mitochondrial genome; Nuclear genes